Apexification with a New Intra-Canal Medicament: A Multidisciplinary Case Report - Soares, Adriana Jesus; Nagata, Juliana Yuri; Casarin, Renato Corrêa Viana; Almeida, José Flávio Affonso; Gomes, Brenda Paula Figueiredo de Almeida; Zaia, Alexandre Augusto; Ferraz, Caio Cezar Randi; Souza-Filho, Francisco José (Iranian Endodontic Journal, 2012)
Dental trauma generally requires multidisciplinary planning and treatment for good prognosis. When immature teeth are traumatized to a degree where pulp necrosis ensues, the objective of root canal treatment should be apexogenesis and root maturation. Apexification of the root is the conventional choice, which involves cleaning the canal and filling it with a temporary medication that stimulates the formation of a calcific apical barrier. Dental Trauma Service of Piracicaba Dental School, State University of Campinas (UNICAMP), Brazil employs a dressing for apexification treatments with calcium hydroxide, chlorhexidine gel 2% and zinc oxide. This paper reports the case of a dental trauma of the maxillary central incisors and subluxation on teeth 11, 12 and 21 that were treated with multidisciplinary collaboration (Endodontics, Periodontology and Operative Dentistry) to improve prognosis. After five-years there were no pathological conditions and the teeth showed every evidences of success.